2006
DOI: 10.1161/01.res.0000247034.24662.b4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Low-Density Lipoprotein–Dependent Endothelial Arginase II Activation Contributes to Impaired Nitric Oxide Signaling

Abstract: Abstract-Oxidized low-density lipoprotein (OxLDL) impairs NO signaling and endothelial function, and contributes to the pathogenesis of atherosclerosis. Arginase reciprocally regulates NO levels in endothelial cells by competing with NO synthase for the substrate L-arginine. In human aortic endothelial cells, OxLDL stimulation increased arginase enzyme activity in a time-and dose-dependent manner. Arginase activity reached its maximum as early as 5 minutes, was maintained for a period of more than 48 hours, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
187
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(198 citation statements)
references
References 38 publications
11
187
0
Order By: Relevance
“…Arginase is reported to reciprocally regulate NOS [29] by modulating L-arginine bioavailability. Arginase upregulation is reported to contribute to impaired NO signaling as a result of aging [45] as well as following treatment of ECs to Ox-LDL [29] and is suggested to be a therapeutic target. However, arginase inhibition failed to affect CRP-mediated eNOS inhibition, excluding arginase upregulation in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Arginase is reported to reciprocally regulate NOS [29] by modulating L-arginine bioavailability. Arginase upregulation is reported to contribute to impaired NO signaling as a result of aging [45] as well as following treatment of ECs to Ox-LDL [29] and is suggested to be a therapeutic target. However, arginase inhibition failed to affect CRP-mediated eNOS inhibition, excluding arginase upregulation in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The activation and expression of endothelial arginase II can also be induced by a variety of vascular stimulants, including OxLDL, LPS, TNF-α, IFN-γ, 8-bromocGMP, and hypoxia [7,10,[12][13][14]. Arginase activation/upregulation results in arginase/NOS imbalance, as well as de-creased NO production, and has been demonstrated to contribute to endothelial dysfunction, in a number of diseases/ pathophysiological processes, including aging [4], diabetes [15][16][17], hypertension [18][19][20], and atherosclerosis [14,21].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been reported that LDL, especially ox-LDL, is a potent inhibitor of endothelial function (19,20). The mechanisms by which LDL inhibits endothelial-derived NO activity include the down-regulation of endothelial NO expression (20,21), decreased receptor-mediated NO release (20), and NO inactivation via increases in O 2 − production (22,23). Indeed, endo thelial dysfunction is a hallmark of hypercholesterolemia and is rapidly improved by cholesterol reduction (24).…”
Section: Introductionmentioning
confidence: 99%